"Journal: 21st Annual Photo Contest - Honorable Mention – Quarrying and Mining Quarry Blast" - Gillian Worsey; Paul Worsey (International Society of Explosives Engineers, 2015)
The basic blasting class at Missouri S&T blast in the quarry at the experimental mine in preparation for the International Intercollegiate Mining (Mucking) Competition in April 2014.